2013
DOI: 10.4271/2013-01-0688
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Advanced Fuzzy Active Steering Controller and a Novel Method to Tune the Fuzzy Controller

Abstract: A two-passenger, all-wheel-drive urban electric vehicle (AUTO21EV) with four direct-drive in-wheel motors has been designed and developed at the University of Waterloo. An advanced genetic-fuzzy active steering controller is developed based on this vehicle platform. The rule base of the fuzzy controller is developed from expert knowledge, and a multicriteria genetic algorithm is used to optimize the parameters of the fuzzy active steering controller. To evaluate the performance of this controller, a computatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…The GFASC developed in [13] has confirmed that superimposing the steering input provided by the driver with a correction generated by the active steering system is considered to be a continuous process, and is not perceived by the driver as being disruptive. It is also advantageous to employ steering intervention rather than braking or driving individual wheels when controlling the vehicle on slippery surfaces, since steering intervention requires less frictional force between the tire and the road to generate a corrective yaw moment.…”
Section: Integration Of the Advanced Torque Vectoring And Genetic Fuzmentioning
confidence: 95%
See 4 more Smart Citations
“…The GFASC developed in [13] has confirmed that superimposing the steering input provided by the driver with a correction generated by the active steering system is considered to be a continuous process, and is not perceived by the driver as being disruptive. It is also advantageous to employ steering intervention rather than braking or driving individual wheels when controlling the vehicle on slippery surfaces, since steering intervention requires less frictional force between the tire and the road to generate a corrective yaw moment.…”
Section: Integration Of the Advanced Torque Vectoring And Genetic Fuzmentioning
confidence: 95%
“…Taking advantage of the strengths of each active chassis subsystem, the ideal traction and stability performance of the vehicle can be obtained by activating the subsystem or subsystems that will be most effective given the deviation between the desired and actual behavior of the vehicle. The performance and effectiveness of the advanced torque vectoring controller (ATVC) and the genetic fuzzy active steering controller (GFASC) were studied and evaluated individually in previous papers [12,13]. In this work, we investigate whether the integration of these stability control systems enhances the performance of the vehicle in terms of handling, stability, path-following, and longitudinal dynamics.…”
Section: Integration Of the Advanced Torque Vectoring And Genetic Fuzmentioning
confidence: 99%
See 3 more Smart Citations